2022
DOI: 10.3390/ijerph19106047
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Workplace Conflicts and Subsequent Physician-Certified Sick Leave: A Prospective Population Study

Abstract: The impact of workplace conflicts on sick leave is largely unknown. We studied the associations between conflicts and physician-certified sick leave in a randomly drawn general working population sample. Eligible respondents were interviewed in 2009, 2013, and 2016 and were registered with an employee relationship ≥50 working days in the national sick-leave register the year following the survey interviews (n = 22,088 observations/13,731 respondents). We used mixed-effects logistic regression models (adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Another review and meta-analysis found moderate evidence for the association between workplace bullying and subsequent sickness absence. 10 The literature was scantier for effects of other psychosocial work factors, such as emotional demands, [11][12][13] demands for hiding emotions/emotional dissonance, 12,14 role conflict, [11][12][13][14][15] low supportive leadership, 13 conflicts with superiors, 16 workplace violence and/or threats of violence, [17][18][19] work-family conflict, 12,20 or job insecurity. 12 A wide range of psychosocial work exposures may be associated with sickness absence, as shown for other health-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another review and meta-analysis found moderate evidence for the association between workplace bullying and subsequent sickness absence. 10 The literature was scantier for effects of other psychosocial work factors, such as emotional demands, [11][12][13] demands for hiding emotions/emotional dissonance, 12,14 role conflict, [11][12][13][14][15] low supportive leadership, 13 conflicts with superiors, 16 workplace violence and/or threats of violence, [17][18][19] work-family conflict, 12,20 or job insecurity. 12 A wide range of psychosocial work exposures may be associated with sickness absence, as shown for other health-related outcomes.…”
Section: Introductionmentioning
confidence: 99%